The consumption values, satisfaction and continuance intention towards ordering from Food Delivery Applications (FDAs) - Lucky, Seemola Mogwasa (Vaal University of Technology, 2024)
The purpose of this study was to explore South African consumers' intention to continue using food delivery applications (FDAs) based on the perceived value of such platforms. While prior predominant scholarship focused on the technical aspects of FDAs, this study sought to establish the predictive influence of selected value dimensions on post-acceptance satisfaction and continued use using the central prescripts of the theory of consumption value and the post-acceptance model of information systems. Understanding the interplay among these variables assists restaurateurs to adapt to evolving consumption patterns. After purposively identifying a select cohort of consumers, an n electronic survey was administered to South African consumers who possess previous usage experience of FDAs. The study successfully obtained compliant cooperation from 371 respondents, providing insights into consumer perceptions and preferences. These findings are essential for improving customer experience and fostering long-term engagement with FDAs in the competitive food delivery landscape. Data were tested for common methods bias using Harman’s factor test. Exploratory factor analysis assisted in reducing the data set to identifiable variables. Hypotheses were tested using the structural equation modelling (PLS-SEM) Version 4.0. The results confirmed that four value dimensions positively impact users’ post-usage satisfaction. However, social value reported a negative impact on post-usage satisfaction (β=-0.152, t=4.067, p=0.000). On the other hand, global customerperceived value strongly influenced post-acceptance satisfaction (β=+0.769, t=20.119, p=0.000). Notably, there was no direct effect between global perceived value and continuance intentions (β=0.014, t=0.161, p=0.872), whereas postacceptance satisfaction strongly and positively influenced consumers’ intention to continue using FDAs in the future (β=+0.367, t=3.800, p=0.000). The results of this study confirm that customer perceived value is a multifaceted construct, comprising functional, social, emotional, epistemic and conditional values, albeit with differing directionality for social value. Interestingly, this could suggest a shift towards independent (solo) buying behaviours in South African consumer culture. In addition, the limited social features of FDAs might not align with the primary motivations for using FDAs, which are convenience and physiological satisfaction. Thus, this study encourages retailers and designers of mobile applications to enhance the experiences of customers by focusing on multiple value dimensions. Furthermore, post-adoption satisfaction positively impacts the intention to continue using FDAs, underscoring the need for retailers to deliver a satisfying initial experience to ensure long-term engagement on the FDA platforms. These insights align with existing research, highlighting customer satisfaction as a key driver of continued FDAs use.
MM (MKT) (Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Food delivery applications (FDAs); Third-party applications; Customer-perceived value; Global-perceived value; Post-acceptance satisfaction; Continuance intention; Dissertation, Academic -- South Africa.; Fast food restaurants -- Marketing.